On the Grobner Basis of the Toric Ideal for 3 X n- Contingency Tables - Mohammed Hussein, Hussein S.; Majeed, Abdulrahman H. (Iraqi Journal of Science, 2019)
In this paper, The Grobner basis of the Toric Ideal for - contingency tables related with the Markov basis B introduced by Hussein S. MH, Abdulrahman H. M in 2018 is found. Also, the Grobner basis is a reduced and universal Grobner basis are shown.